Scientology a new slant on life - Hubbard, L. Ron (La Fayette Ron) 1911-1986 (Bridge Publications, Inc., 2007)
What are your goals? Where are you going? Why are you here? What are you? Scientology has answers to these questions, good answers that are true, answers that work for you. For the subject matter of Scientology is you.